SUN-107 Abdominal Adipose Stem Cell Dysfunction In Vitro May Reflect Adipose Insulin Resistance In Vivo in Normal Weight Polycystic Ovarian Syndrome Women - Leung, Karen (J Endocr Soc, 2019)
Subcutaneous (SC) abdominal adipose stem cells (ASCs) of normal-weight polycystic ovary syndrome (PCOS) women show exaggerated development to newly-formed adipocytes in vitro (1). To determine whether this phenomenon in PCOS was related to adipose insulin resistance (adipose-IR) in vivo, 8 normal-weight PCOS women and 8 age- and BMI-balanced controls underwent circulating androgen and fasting insulin/free fatty acid (FFA) measurements. SC abdominal ASCs were isolated by fat biopsy and cultured in adipogenic medium for 12 days. ASC commitment to preadipocytes and newly-formed adipocytes derived from preadipocytes were determined by ZFP423 protein expression on day 0 and cellular lipid content by Oil Red O staining on day 12, respectively (i.e. adipogenesis). Adipose-IR was calculated as the product of fasting circulating FFA and insulin levels (2). Student’s t-test compared serum androgen levels and adipose-IR by female type; partial correlation coefficients examined associations of ZFP423 protein expression and newly-formed adipocyte lipid content with adipose-IR, adjusting for androgen levels. PCOS women had greater serum total testosterone [T] and free [f] T (P<0.005, both androgens) levels and higher adipose-IR (P=0.01) than controls. Newly-formed adipocyte lipid content positively correlated with adipose-IR in all women combined (R=0.57, P=0.02), however, significance was lost when adjusted for serum androgen levels (R=0.44, P=0.10 and R=0.36, P=0.18, for total T and fT, respectively). ZFP423 protein expression was not significantly correlated with adipose-IR in all women combined (R=-0.28, P=0.29), but was negatively correlated with adipose-IR (R=-0.64, P=0.01) after adjusting for total T levels. Using exploratory subgroup analysis, the positive relationship of newly-formed adipocyte lipid content with adipose-IR was significant in PCOS women (R=0.67, P=0.05) but not in controls (R=0.10, P=0.80). Similarly, the negative relationship of ZFP423 protein expression with adipose-IR was characteristic of PCOS women (R=-0.88, P=0.002) but not controls (R=-0.26, P=0.50). Thus, given the limited number of subjects, we hypothesize that altered SC abdominal adipogenesis contributes to increased adipose-IR in normal-weight PCOS women and that this relationship is due in part to hyperandrogenism. References: (1) Fisch SC, et al. Fertil Steril 2018; in press. (2) Sondergaard E, et al. JCEM 2017;102:1193. Sources of Research Support: NIH Grants and Santa Monica Bay Woman’s Club.